2021
DOI: 10.3389/fphar.2021.680178
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Treatment of Pulmonary Infections: An Umbrella Review and Evidence Map

Abstract: Background: Considering the global burden of pulmonary infections, there is an urgent need for optimal empirical antimicrobial therapy strategies for pulmonary infections, which should rely on reliable evidence. Therefore, we aim to investigate the optimal treatment options for pulmonary infections in adults and assess the strength of that evidence.Methods: We searched PubMed, Embase, the Cochrane Library, and China Biology Medicine disc to identify systematic reviews and meta-analyses of randomized controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
(102 reference statements)
0
4
0
Order By: Relevance
“…Recommended empiric antibiotic treatment can be read in table 2 . Guidelines worldwide recommend a combination of a beta-lactam plus macrolide or quinolone [ 29 , 96 98 ]. Due to potential serious adverse effects of quinolones [ 61 ] and proven benefits of macrolide combinations of 3 days, this last is the preferred option.…”
Section: Resultsmentioning
confidence: 99%
“…Recommended empiric antibiotic treatment can be read in table 2 . Guidelines worldwide recommend a combination of a beta-lactam plus macrolide or quinolone [ 29 , 96 98 ]. Due to potential serious adverse effects of quinolones [ 61 ] and proven benefits of macrolide combinations of 3 days, this last is the preferred option.…”
Section: Resultsmentioning
confidence: 99%
“…Therapeutic approaches aimed at enhancing the lung microbiome for respiratory well-being are promising avenues for managing airway diseases. Studies have explored diverse strategies to modulate the lung microbiome, including probiotic supplementation, antimicrobial therapy, and microbiota transplantation (Mortaz et al 2013 ; Chmiel et al 2014 ; Jang et al 2020 ; Wu et al 2021 ; Du et al 2022 ). For example, Yeo et al ( 2014 ) demonstrated the potential of probiotics containing Lactobacillus fermentum CJL-112 strain to prevent influenza virus infection by activating the T-helper cells.…”
Section: Therapeutic Approaches: Strategies For Enhancing Lung Microb...mentioning
confidence: 99%
“…Recommended empiric antibiotic treatment can be read in table 2. Guidelines worldwide recommend a combination of a beta-lactam plus macrolide or quinolone [29,[96][97][98]. Due to potential serious adverse effects of quinolones [61] and proven benefits of macrolide combinations of 3 days, this last is the preferred option.…”
Section: E a T T A Tmentioning
confidence: 99%